LATIHAN PERNAPASAN DIAFRAGMA MENINGKATKAN KAPASITAS PARU-PARU PADA ATLET TAEKWONDO PUTRA DI CLUB DYNASTY TNI AL DENPASAR, BALI - Nohantara, Made Ari; Putriyani, Putu Sintya (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
One of the most needed components of a taekwondo athlete is endurance so they don’t get tired and can maintain performance during matches. Cardiorespiratory endurance can be determined by measuring the value of lung vitality. Pulmonary vitality values can be done using a spirometry measuring instrument. The purpose of this study was to find out that diaphragmatic breathing increases lung vitality in male Taekwondo athletes at the Denpasar Bali Navy Club. This research is a pilot study with a single-group pretest-posttest design. The sample in this study consisted of 10 Taekwondo athletes. The sampling technique for this study used a purposive sampling technique. Diaphragmatic breathing exercises are carried out for 4 weeks with a frequency of exercise 4 times a week, duration of 1 set, 1 set of 20 repetitions. In this study, a spirometer was used to measure lung vital capacity. The results of testing the hypothesis with the paired t test showed that diaphragmatic breathing increases the lung vital capacity of Taekwondo athletes in the TNI AL Dynasty Club by 18.79 percent with a significant probability value (p). that is, p = 0.000. Diaphragmatic breathing significantly increases lung vital capacity of Taekwondo athletes in the TNI AL Dynasty Club.